A New Dispersion Medium for the Direct Slurry Atomization Electrothermal Atomic Absorption Spectrophotometric Determination of Magnesium in Carbon-black and Lampblack - Khammas Zuhair, A.A.; Manasreh, Walled; Fadhil, Jasim (Asian Journal of Chemistry, 2010)
A new method has been developed for the formation of fine and stable slurry by mixing a few milligrams of carbon-black or lampblack samples with a mixture of xylene and 2- ethylhexanoic acid using ultrasonic vibration for a few minutes and the resulting slurry is dispensed directly into a graphite furnace to obtain the atomic vapours of the constituents of these samples. The developed method has been applied for the determination of magnesium at trace levels in these matrices by the construction of calibration graph using an organomagnesium (Mg 4-cyclohexylbutyrate) as a primary standard dissolved in the abovementioned organic mixture. At optimum conditions a linear range up to 20 μg L-1 with absolute sensitivity of 0.21 pg, method detection limit of 1.2 pg and RSD within a linear range from 9.71 to 1.96 % are obtained. The recovery percentage is reported as from 84-106 %. The atomization mechanism of Mg in this medium is also investigated. The described method could be applicable to other trace metals in these matrices and in the meantime avoids interferences in case of aqueous calibrant (containing trace contaminants) are used instead.